Offending behaviour programmes in the community: the effects on reconviction of three programmes with adult male offenders - Palmer, Emma J. (Legal and criminological psychology, 2007)
Purpose. This study presents the findings of an evaluation of the effect on reconviction of three general offending behaviour programmes in the English and Welsh Probation Service with adult male offenders. Method. The study employed a quasi-experimental design comparing the reconviction rates of three groups: offenders who were allocated to and completed a programme, offenders allocated to a programme but failed to complete, and a comparison group. Results. The main finding from the analyses indicated that, controlling for salient population factors, the offenders who had completed a programme had a lower rate of reconviction as compared with non-completers and comparison groups. Additionally, the non-completers had a higher rate of reconviction than the comparison group. Conclusions. The findings are discussed in light of the extant literature and a range of explanations is presented.